USM ACKNOWLEDGES STUDENT LEADERS FOR THEIR INVOLVEMENT IN PLANNING PROGRAMMES - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 12 October 2015 – Universiti Sains Malaysia (USM) intends to highly acknowledge members of the Students Representative Council (MPP) from their involvement with the top management in drawing up future plans for the university, with their participation in the 9 Key Focus Areas, aimed be achieved within the next 5 years.